2021
DOI: 10.3390/biomedicines9101469
|View full text |Cite
|
Sign up to set email alerts
|

Link between History of Childhood Maltreatment and Emotion Dysregulation in Adults Suffering from Attention Deficit/Hyperactivity Disorder or Borderline Personality Disorder

Abstract: Childhood maltreatment (CM) may have a long-term effect on emotion regulation. This study aimed to explore the relationship between CM and emotion dysregulation (ED) in a heterogeneous population. Four hundred seventy French-speaking outpatients (N = 279 ADHD, N = 70 BPD, N = 60 ADHD + BPD, N = 61 clinical controls) completed the Emotion Reactivity Scale (ERS), the Cognitive Emotional Regulation Questionnaire (CERQ), the Childhood Trauma Questionnaire (CTQ), and the Relationship Scales Questionnaire (RSQ). Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 106 publications
2
10
0
Order By: Relevance
“…In addition to the contribution of ED to the functional impairment associated with adult ADHD, our results suggest a weak, albeit signi cant contribution of childhood maltreatment to ED and sleep problems. This is consistent with a number of studies suggesting that environmental factors and especially childhood maltreatment are involved in the development and the severity of ED in ADHD (54), similar to other disorders, such as BPD and BD (54,99,100).…”
Section: Multiple Linear Regression Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to the contribution of ED to the functional impairment associated with adult ADHD, our results suggest a weak, albeit signi cant contribution of childhood maltreatment to ED and sleep problems. This is consistent with a number of studies suggesting that environmental factors and especially childhood maltreatment are involved in the development and the severity of ED in ADHD (54), similar to other disorders, such as BPD and BD (54,99,100).…”
Section: Multiple Linear Regression Analysessupporting
confidence: 92%
“…Indeed, compared to healthy peers, adults with ADHD report increased childhood traumatic events (51), and maltreated children often present with ADHD (52,53). Of note, a recent study led by Rüfenacht et al (54) found that self-reported emotional neglect and abuse during childhood contributed to emotional reactivity and poor emotion regulation strategies independently of the clinical presentation of adult ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in BD patients, inflammatory biomarkers have been identified in ER-associated brain regions, such as the hippocampus (69). Recent cross-sectional evidence from ADHD and BPD has also revealed that a history of childhood maltreatment, which has been associated with increased peripheral inflammation in humans (70)(71)(72)(73), is linked to maladaptive emotional responses in adulthood (74). A vicious cycle may therefore exist in EDD, in which stress and the associated proinflammatory state disrupt limbic connectivity, exacerbating ED symptoms and exposing patients to further stress and immune dysregulation.…”
Section: Emotion Regulation and (Neuro)inflammation In Emotion Dysreg...mentioning
confidence: 99%
“…Several lines of evidence can be marshalled to support that ELS is associated with heightened systemic inflammation (142)(143)(144)(145)(146)(147) and ED (74,105,(148)(149)(150)(151). Not surprisingly, childhood trauma, a specific form of ELS, confers a heightened risk for developing psychiatric disorders transdiagnostically (152).…”
Section: Mechanismsmentioning
confidence: 99%
“…This study provides us with new insight in the pathophysiology of ADHD, opening a new way to improve the diagnosis of ADHD, based on plasma levels of these lipid species. Rüfenacht and colleagues [7], based on a sample of 470 French-speaking outpatients (N = 279 ADHD, N = 70 BPD, N = 60 ADHD + BPD, N = 61 clinical controls) emphasize the importance of early life adversities in the aetiology of emotion dysregulation in ADHD. They also highlight the mediating effect of insecure attachment in the relationship between history of childhood maltreatment and emotion reactivity and the use of non-adaptive cognitive emotion regulation strategies in adult ADHD.…”
mentioning
confidence: 99%